Characteristics of droplets ejected from liquid glycerol doped with carbon in laser ablation propulsion - 郑志远 张思齐 梁田 高禄 高华 张自力 (Chinese physics B, 2016)
The characteristics of droplets ejected from liquid glycerol doped with carbon are investigated in laser ablation propul- sion. Results show that carbon content has an effect on both the coupling coefficient and the specific impulse. The doped- carbon moves the laser focal position from the glycerol interior to the surface. This results in a less consumed glycerol and a high specific impulse. An optimal propulsion can be realized by varying carbon content in glycerol.